2020
DOI: 10.15416/ijcp.2020.9.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Its Factor in Type 2 Diabetic Patients in Jakarta

Abstract: Poor glycemic control is a primary risk factor for the progression of complications. This study aimed to determine the status of glycemic control and associated factors among type 2 Diabetes Mellitus (DM) patients at primary health care of Cakung District, Kebon Jeruk District and Rawa Bunga Village, Jakarta. This study was conducted from July to August 2019, and adopted a cross-sectional design. The respondents' data included sex, age, occupation, education, long suffered with diabetes, diagnosed chronic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…This systematic review included 12 articles that met the eligible criteria (Table 1) [16][17][18][19][20][21][22][23][24][25][26][27]. The included articles were published either in 2021 [16][17][18][19][20][21][22] or in 2020 [23][24][25][26][27]. No articles were published in 2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This systematic review included 12 articles that met the eligible criteria (Table 1) [16][17][18][19][20][21][22][23][24][25][26][27]. The included articles were published either in 2021 [16][17][18][19][20][21][22] or in 2020 [23][24][25][26][27]. No articles were published in 2022.…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 cross-sectional studies [16,[18][19][20][21][22][23][24][25]27], whereas the remaining two studies were either retrospective observational [17] or retrospective [26]. Among the cross-sectional studies, there were seven studies that reported a cross-sectional design only [18][19][20][22][23]25,27], whereas the remaining three studies reported that the studies were prospective cross-sectional [16], descriptive-analytical cross-sectional [21], and descriptive cross-sectional [24]. The overall prevalence of poor glycemic control was 45.2%…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Studies related to metformin efficacy either monotherapy or combination in Indonesian population found that our patients tend to have poor glycemic control. 6–8 …”
Section: Introductionmentioning
confidence: 99%